Removal of Birlliant Green Dye From Aqueous Solution by Adsorption Onto Modified Clay - Al-Mammar, Dunya Edan (Ibn AL-Haitham Journal For Pure and Applied Sciences, 2017)
Application of a Fe-bentonite nano clay (Fe-BNC) as modified clay has been investigated for the removal of birlliant green (BG) from aqueous solutions. Atomic force microscope measurements give a detailed information on pore shape and pore size distribution about the clay. These measurements show that the average diameter of the improved clay is 346.84 nm. Batch adsorption experiments were carried out for the removal of (BG) from aqueous solutions onto Fe-BNC. Equilibrium data were fitted to Freundlich and Langmuir isotherm equations and the isotherm constants were determined. Thermodynamic parameters such as free energy, entropy and enthalpy, have been calculated. For the modified clay the study of adsorption rate constants has been carried out using lagergrens first order rate equations for the adsorption processes and it is found to follow first order rate kinetics. In addition, an activation energy of sorption has also been determined.